Huntingtin Nuclear Localization: Current Insights into Mechanism and Regulation - Desmond, Carly R. (My University, 2013)
Huntington's Disease brains display a striking accumulation of huntingtin in the nucleus of striatal and cortical neurons, suggesting that nuclear functions may be key to the onset of cellular pathogenesis. Entry to the nucleus is tightly regulated by a family of import receptors called karyopherins that limit their binding to proteins bearing specific nuclear localization signals (NLS). Although huntingtin is primarily cytoplasmic in healthy neurons, it is also found in the nucleus at low levels and contains a nuclear export signal (NES), suggesting that shuttling to and from the nucleus is part of the protein's normal function. Indeed, recent publications from our lab (Atwal et al. 2007 and 2011, and Munsie et al. 2011) describe huntingtin's ability to enter the nucleus in response to cell stress, and localize to cofilin-actin rods. We have identified an active NLS near the amino terminus of huntingtin between amino acids 174-207, which is recognized by both karyopherin β2 and β1. While functional in STHdh and NIH 3T3 cells, the huntingtin NLS lacks activity in HEK 293 and MCF-7 cell lines. This surprising observation suggests that additional levels of regulation exist amongst cell types. We have isolated a shorter sequence within the NLS that localizes to membrane structures throughout the cell (such as the plasma membrane and vesicles). This thesis explores several putative secondary regulatory mechanisms, such as, nuclear export activity, transcriptional dependence, palmitoylation and acetylation. However, the most promising mechanism thus far is masking of the NLS by HAP1 and HMGB1. The functions of these proteins, in vesicular trafficking and autophagy/apoptosis, respectively, may offer further insight into huntingtin’s nuclear function. By understanding the underlying regulatory mechanisms of huntingtin nuclear import, we hope to gain further insight into why huntingtin accumulates in the nucleus of specific neurons in HD, and whether or not this mislocalization directly contributes to disease.
Keywords: Huntington's Disease; Nuclear Transport; Huntingtin; Cell Biology; Cell Biology